English Language Teaching in Multilevel Classrooms: Challenges and Opportunities - Banstola, Pitri Raj (English Language Teaching Perspectives, 2023)
ELT classes in the schools of Nepal greatly vary in terms of number of the students in classroom. Large classes become multilevel and can have both challenges and opportunities for English language teachers. Therefore, this paper aims at exploring the challenges and opportunities of teaching English in large multilevel classes. Selecting five classes from five different schools in Pokhara city purposively, I observed ELT classes and interviewed the English language teachers to collect information. It has been found that teaching English in large multilevel classes is challenging though it has brought opportunities for English teachers. Engaging students in the lessons, correcting huge amounts of written work, evaluating students and keeping their records, paying equal attention to all the students and getting the quiet students active are the challenges. However, having enough students for interaction and collecting new experiences from the large classes to develop professional competence are opportunities for English teachers.